FINANCIAL FEASIBILITY ANALYSIS OF VANDA DOUGLAS ORCHID ORNAMENTAL PLANT BUSINESS IN GUNUNG SINDUR DISTRICT, BOGOR REGENCY - Siti Rochaeni; Titik Inayah; Wildha Ainun Ritonga (AGRIBUSINESS JOURNAL, 2021)
Ornamental plants are widely used to beautify yards and gardens. In addition, many types of ornamental plants are used as businesses that generate profits. Ornamental plant business activities have great potential to be developed by an effort to grow the national and regional economies. One of the ornamental plants that have the potential to be developed is orchids.The objectives of this study are calculating the business costs of vanda douglas orchid ornamental plants in Gunung Sindur District. Analyzing the business income of vanda douglas orchid ornamental plants in Gunung Sindur District. Analyzing the business prospects of vanda douglas orchid ornamental plants in Gunung Sindur district using, B/C Ratio, Break Event Point (BEP), Payback Period (PP), Net Present Value (NPV), and Internal Rate of Return (IRR). This research was conducted on orchid farmers in Gunung Sindur District with a population of 30 respondents. The data used in this study are primary data and secondary data. The data and information that has been collected are analyzed qualitatively and quantitatively which is processed with the help of Microsoft Excel Software.The results showed that the business costs carried out by vanda Douglas orchid farmers in Gunung Sindur District during the planting season amounted to Rp. 162,775,000, consisting of fixed costs of Rp. 46,574,400 and variable costs of Rp. 143,075,000. Income Rp. -33,775,000, receipts Rp. 129,000,000. The B/C value ratio of -0.20 indicates that the B/C value ratio is less than zero, the BEP of production volume is 1,627 bunches and the BEP price is Rp. 126,182, the payback period of -4.16 years the value of the Payback Period shows that the vanda Douglas orchid business is negative, which means that farmers have not been able to return investment because they are losing money. Then the NPV value of the orchid business was Rp. -194,401,493 and was negative and the IRR value was 1.68% < 2%. So, it can be concluded that the vanda Douglas orchid business carried out by farmers in Gunung Sindur District does not provide benefits and is not feasible to run in the future.